PENINGKATAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI PERMAINAN KARTU ANGKA ANAK USIA 5-6 TAHUN DI TK TUNAS KASIH KOTA MAKASSAR - Endang Ruswiyani (Fakultas Keguruan dan Ilmu Penidikan UIM, 2018)
This study aims to improve the ability to recognize the concept of numbers through number playing cards for Group B children at TK Tunas Kasih Makassar. The type of research used is Classroom Action Research conducted collaboratively between researchers and classroom teachers. The technique of collecting data through observation and documentation. The instrument used is the observation sheet (check list). Data analysis techniques were carried out in qualitative and quantitative descriptive. The results of the study showed that there was an increase in the ability to recognize the concept of numbers after learning through the activity of playing cards. The percentage in cycle I is the child who develops according to expectations, there are 7 children (63.64%) while in silus II has achieved the success indicator, namely children who develop according to expectations there are 4 children (27.27%), while children who develop very well (BSB) there are 7 children (54.55%).Keywords: Concept of Numbers, Number Card Games.